Collaboration of Hexahelix In Developing Natural Tourism Potential - Dading Fajarudin; Nana Setiana; Unen Supriadi; Moh. Taufik Hidayat; Hery Nariyah (Journal Research of Social Science, Economics, and Management, 2024)
Kuningan Regency is located in the province of West Java which borders Central Java province, with good natural resources to be developed into tourism and becoming one of the sources of Regional Budget Revenue (PAD), so with this we conducted research on tourism in Kuningan Regency with The method we use is a qualitative method, namely by collecting data. From these results, it turns out that tourism is not yet optimal in Kuningan Regency due to the budget and lack of participation by the government and private sector in increasing tourism in Kuningan Regency. To increase tourism, collaboration between stakeholders is needed. The research results show that in the collaboration process carried out in developing tourism potential in the National Nature Tourism Park in Kuningan Regency, this cross-sector collaboration is effective in achieving sustainable development goals, especially at the village level. The success of this program illustrates the potential of the Hexa Helix collaborative model as a solution to global challenges.